AKTIVITAS OLAHRAGA YANG DILAKUKAN MASYARAKAT PADA MASA PANDEMI COVID-19 DI KOTA BANDA BERDASARKAN USIA - Didi Yudha Pranata (Universitas Sriwijaya, 2020)
The purpose of this study is to find out what sports the community does during the Covid 19 pandemic in the city of Banda Aceh based on their age. Descriptive research method with survey techniques. The sampling technique was using random sampling techniques, the object was 350 people. Data collection techniques using google form. The data analysis technique used descriptive statistics. The results showed that the people of Banda Aceh, aged 16 to 25 years, 53% of the people did jogging during the Covid-19 pandemic, 22%, cycling and 25% of other sports such as walking, martial arts and grub sports. Ages 26 to 35 years 31% of people did jogging during the Covid-19 pandemic, 25%, cycling and 44% of other sports such as martial arts, gymnastics, yoga, walking, badminton and grub. Age 36 years and over 35% of people do jogging during the Covid-19 pandemic, 30% are cycling and 35% of other sports such as walking, badminton, agility and martial arts. The conclusion from the results of this study is that during the Covid-19 pandemic, the people of Banda Aceh city continued to carry out sports activities such as jogging, cycling, walking and other individual sports. His suggestion is that after sports activities, people should no longer gather or rest in public areas, but instead return to their homes to avoid crowds.